Policy Assemblages Of Learning‑To‑Learn And Innovation: Mapping Metacognition And Design Thinking (International Journal of Environmental Sciences, 2025)
Metacognition,  the conscious awareness and regulation of one’s own thinking ,  and design thinking, an iterative, human‑centred approach to solving problems ,  are increasingly championed as twin engines of learner agency. India’s National Education Policy, adopted in 2020, positions both constructs at the heart of curriculum renewal, yet little is known about how these ideas journey from global discourse into local praxis across the country’s diverse educational landscapes. Guided by policy‑mobility theory, critical discourse analysis, and decolonial perspectives, this paper maps the translation of metacognition and design thinking through policy texts, teacher‑education initiatives, and classroom practice. A qualitative synthesis of international reports, peer‑reviewed scholarship, and Asia‑Pacific case studies reveals four interwoven patterns: convergence on skills for the contemporary era, context‑specific redesign of design‑thinking toolkits, reframing of metacognitive scaffolding as a vehicle for equity, and hybrid assessment reforms that capture reflective practice. The study proposes a multilayered framework for researchers and policymakers seeking culturally responsive, strategically aligned implementation of these powerful pedagogical ideas.